2021
DOI: 10.3390/ijms22179619
|View full text |Cite
|
Sign up to set email alerts
|

New Glycosylated Dihydrochalcones Obtained by Biotransformation of 2′-Hydroxy-2-methylchalcone in Cultures of Entomopathogenic Filamentous Fungi

Abstract: Flavonoids, including chalcones, are more stable and bioavailable in the form of glycosylated and methylated derivatives. The combined chemical and biotechnological methods can be applied to obtain such compounds. In the present study, 2′-hydroxy-2-methylchalcone was synthesized and biotransformed in the cultures of entomopathogenic filamentous fungi Beauveria bassiana KCH J1.5, Isaria fumosorosea KCH J2 and Isaria farinosa KCH J2.6, which have been known for their extensive enzymatic system and ability to per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…The reduction of the double bond of chalcones has been observed in the cultures of many microorganisms, as we highlighted in our previous work [ 29 ], the same as glycosylation of dihydrochalcones [ 41 ]. Our innovation is to perform these reactions simultaneously in one pot using extensive enzymatic systems of the selected strains of entomopathogenic filamentous fungi [ 29 ]. These fungi naturally produce enzymes to penetrate the insect’s cuticle.…”
Section: Resultsmentioning
confidence: 53%
See 4 more Smart Citations
“…The reduction of the double bond of chalcones has been observed in the cultures of many microorganisms, as we highlighted in our previous work [ 29 ], the same as glycosylation of dihydrochalcones [ 41 ]. Our innovation is to perform these reactions simultaneously in one pot using extensive enzymatic systems of the selected strains of entomopathogenic filamentous fungi [ 29 ]. These fungi naturally produce enzymes to penetrate the insect’s cuticle.…”
Section: Resultsmentioning
confidence: 53%
“…Our previous and other teams’ studies showed that entomopathogenic filamentous fungi can be a valuable tool in the biotransformation of phenolic compounds, especially flavonoids, including 4″- O -methylglucosylation and hydroxylation [ 23 , 25 , 28 , 29 , 30 , 31 , 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations